2021
DOI: 10.1002/ps.6433
|View full text |Cite
|
Sign up to set email alerts
|

Remote monitoring of Cydia pomonella adults among an assemblage of nontargets in sex pheromone‐kairomone‐baited smart traps

Abstract: BACKGROUND Captures of codling moth, Cydia pomonella (L.), in traps are used to establish action thresholds and time insecticide sprays. The need for frequent trap inspections in often remote orchards has created a niche for remote sensing smart traps. A smart trap baited with a five‐component pheromone‐kairomone blend was evaluated for codling moth monitoring among an assemblage of other nontargets in apple and pear orchards. RESULTS Codling moth captures did not differ between the smart trap and a standard t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
(85 reference statements)
1
7
0
Order By: Relevance
“…The unintended catch of nontargets in light traps has been a major concern impacting the sorting and counting of the targeted species (Kim et al, 2019;Madsen & Sanborn, 1962). Ecological impacts from the broad-spectrum effect of lights on human health as well as insect (Frewin et al, 2022;Preti, Favaro, et al, 2020;Suto, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The unintended catch of nontargets in light traps has been a major concern impacting the sorting and counting of the targeted species (Kim et al, 2019;Madsen & Sanborn, 1962). Ecological impacts from the broad-spectrum effect of lights on human health as well as insect (Frewin et al, 2022;Preti, Favaro, et al, 2020;Suto, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Further studies should compare the effectiveness of lure baited traps with LED lights to monitor more than one tortricid pest in orchards, and consider different wavelength emission ranges. Adoption of “smart traps” with remote visual identification software could benefit from simultaneous accurate counts of multiple pest populations (Frewin et al, 2022; Preti, Favaro, et al, 2020; Suto, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…However, manual confirmation is also a part of the customer service [18]. Cirjak et al [1] claimed that the Trapview standard model had a problem with detecting other objects than the target insect while Preti et al [61] observed that the system incorrectly detects morphologically similar insects. The original Z-Trap system is also not perfect.…”
Section: Discussion On Moth Counting Methodsmentioning
confidence: 99%
“…There are many benefits to using automated pest monitoring equipment (Figure 2). Excessive use of pesticides and time spent on hard-to-reach work decreases, as do daily trips to inaccessible orchards [53][54][55]. However, depending on the pest control method, the pheromones and adhesive pads may need to be replaced occasionally to perform any maintenance [54].…”
Section: Automatic Pest Monitoring Systemsmentioning
confidence: 99%